Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1371/journal.pone.0185937
|View full text |Cite
|
Sign up to set email alerts
|

Adipose-derived stem cells attenuate pulmonary microvascular hyperpermeability after smoke inhalation

Abstract: BackgroundPulmonary edema is a hallmark of acute respiratory distress syndrome (ARDS). Smoke inhalation causes ARDS, thus significantly increasing the mortality of burn patients. Adipose-derived stem cells (ASCs) exert potent anti-inflammatory properties. The goal of the present study was to test the safety and ecfficacy of ASCs, in a well-characterized clinically relevant ovine model of ARDS.MethodsFemale sheep were surgically prepared. ARDS was induced by cooled cotton smoke inhalation. Following injury, she… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 50 publications
(42 reference statements)
0
17
0
Order By: Relevance
“…16,17 Substantial investigation has demonstrated that MSCs are beneficial for the treatment of ALI in preclinical models, including rodents and human tissues. 17,18 In addition, different sources of MSCs, including human amnion-derived MSCs, 19 adipose-derived stem cells, 20 bone-marrow MSCs (BMMSCs), 14,21,22 and nonmuscle myosin IIA-silenced BMMSCs (NM-IIA BMMSCs), 23 were effective in SI-ALI animal models (Table 1). The results of these studies showed that the wet/dry (W/D) ratio in lungs was significantly reduced, and partial pressure of oxygen (PaO 2 ) and the PaO 2 /FiO 2 ratio (where FiO 2 is the fraction of inspired oxygen) were significantly improved after delivery of MSCs.…”
Section: Latest Treatment Progress For Si-alimentioning
confidence: 99%
“…16,17 Substantial investigation has demonstrated that MSCs are beneficial for the treatment of ALI in preclinical models, including rodents and human tissues. 17,18 In addition, different sources of MSCs, including human amnion-derived MSCs, 19 adipose-derived stem cells, 20 bone-marrow MSCs (BMMSCs), 14,21,22 and nonmuscle myosin IIA-silenced BMMSCs (NM-IIA BMMSCs), 23 were effective in SI-ALI animal models (Table 1). The results of these studies showed that the wet/dry (W/D) ratio in lungs was significantly reduced, and partial pressure of oxygen (PaO 2 ) and the PaO 2 /FiO 2 ratio (where FiO 2 is the fraction of inspired oxygen) were significantly improved after delivery of MSCs.…”
Section: Latest Treatment Progress For Si-alimentioning
confidence: 99%
“…Treatment groups were noted to have improved pulmonary function demonstrated by improved PaO 2 /FiO 2 ratio, oxygenation index, and improved peak airway pressures. In addition, these animals also had improvement in the pulmonary microvascular hyperpermeability seen after smoke inhalation injury which was evident by decreased lung lymph flow and increased plasma protein levels when compared to control animals that did not receive stem cell therapy [19].…”
Section: Stem Cell Therapymentioning
confidence: 87%
“…Ihara et al investigated the effect of adipose-derived mesenchymal stem cells on pulmonary microvascular changes using a sheep model of smoke inhalation injury [19]. Sheep were exposed to cotton smoke and then divided into groups that either received adipose-derived stem cells or a control vehicle.…”
Section: Stem Cell Therapymentioning
confidence: 99%
“…sheep and cattle) are limited. Of note, Ihara et al [52] used an ovine model of acute respiratory distress syndrome (ARDS) induced by smoke inhalation to estimate the efficacy of intravenously administrated ASCs. It has been shown that ASCs delivered at a dose of 2.0 × 10 8 cells, rem a r k a b l y r e d u c e d p u l m o n a r y m i c r o v a s c u l a r hyperpermeability, significantly ameliorating pulmonary gas exchange and improving the oxygenation index.…”
Section: In Vivo Study With Domestic Animal Ascsmentioning
confidence: 99%